An Experimental Study on the Strength and Crack Healing Performance of E. coli Bacteria-Induced Microbial Concrete. (15th April 2022) - Islam, Md. Mahfuzul; Hoque, Nusrat; Islam, Moinul; Ibney Gias, Imteaz
Abstract : The most commonly used building material in the construction industry is concrete. However, the weak features of concrete are its low ductility and limited tension capacity and hence crack development with the increase in load. These cracks get more worsened by the intrusion of water and salt present in the composition and hence causing deterioration and reducing the longevity of the material. This study focuses on an innovative approach to mitigate concrete's fractures and flaws by utilizing microbiologically induced calcite (CaCO3 ) precipitation (MICP) excited by Escherichia coli ( E. coli ) bacteria to improve the performance of cementitious building materials. The study investigated the development of microbiological concrete in plain water using only one culture density (OD600 0.5 ± 0.1). In this study, two water-to-bacterial mix ratios (75 : 25 and 50 : 50) were used and compared to the conventional concrete (100 : 0). 100-mm cube-sized specimens cured for a period of 7, 28, 90, and 365 days were tested for compressive strength, water absorption capacity, ultrasonic pulse velocity (UPV), and SEM analysis, which were performed on the samples at regular intervals. According to the results of these experiments, microbial concrete with the 50 : 50 ratio exhibited the highest strength for all curing times. From the water absorption test of samples, it is found that the absorption of the materials got reduced due to the infusion of microorganisms in concrete. On the other hand, the UPV test showed high velocity than the control samples for specimens with an OD600 0.5 ± 0.1. Scanning electron microscope (SEM) analysis performed on distinct concrete groups at the age of 28 days showed fewer voids in the concrete lumps due to the increase in water substitution rate caused by microbial culture.